Improving Students' Critical Thinking Ability through Learning Local History of Tanggomo with Contextual Teaching and Learning Approach at SMAN 03 Gorontalo - Djulia Indriani AH Mahmud; Warto Warto (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to determine the relevance of local history learning to increasing critical thinking skills. Today's critical thinking skills have become the main ability students must have, but the history learning application which still tends to focus on improving students' cognitive by requiring students to memorize historical facts, makes students not have the opportunity to think critically. The lack of discussion of local history is also a problem in itself for learning history, even though local history can help students find meaning in learning history by examining events that are close to the student's environment. This study used a quasi-experimental method with a two-group pretest and posttest design. The results obtained indicate that historical learning that integrates local history using a contextual teaching and learning approach can improve students' critical thinking skills, this can be proven by the t test which was carried out by obtaining a significance of 0.00 <0.05, meaning that there is a significant and positive influence on history learning. local to improve students' critical thinking skills.